External Validation of the Risk Assessment Model of the International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) for Medical Patients in a Tertiary Health System. Issue 6 (17th November 2014) - Rosenberg, David; Eichorn, Ann; Alarcon, Mauricio; McCullagh, Lauren; McGinn, Thomas; Spyropoulos, Alex C.
Abstract : Background: Hospitalized medical patients are at risk for venous thromboembolism (VTE). Universal application of pharmacological thromboprophylaxis has the potential to place a large number of patients at increased bleeding risk. In this study, we aimed to externally validate the International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) VTE risk assessment model in a hospitalized general medical population. Methods and Results: We identified medical discharges that met the IMPROVE protocol. Cases were defined as hospital‐acquired VTE and confirmed by diagnostic study within 90 days of index hospitalization; matched controls were also identified. Risk factors for VTE were based on the IMPROVE risk assessment model (aged >60 years, prior VTE, intensive care unit or coronary care unit stay, lower limb paralysis, immobility, known thrombophilia, and cancer) and were measured and assessed. A total of 19 217 patients met the inclusion criteria. The overall VTE event rate was 0.7%. The IMPROVE risk assessment model identified 2 groups of the cohort by VTE incidence rate: The low‐risk group had a VTE event rate of 0.42 (95% CI 0.31 to 0.53), corresponding to a score of 0 to 2, and the at‐risk group had a VTE event rate of 1.29 (95% CI 1.01 to 1.57), corresponding to a score of ≥3. Low‐risk status for VTE encompassed 68% of the patient cohort. The area under the receiver operating characteristic curve was 0.702, which was in line with the derivation cohort findings. Conclusions: The IMPROVE VTE risk assessment model validation cohort revealed good discrimination and calibration for both the overall VTE risk model and the identification of low‐risk and at‐risk medical patient groups, using a risk score of ≥3. More than two thirds of the entire cohort had a score ≤2.